2020
DOI: 10.17756/jfcn.2020-085
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, Physical and Sensory Properties of Pawpaw Fortified Pan Bread

Abstract: Micronutrient deficiency is a major health problem among children and pregnant women in developing countries. Vitamin A deficiency can be prevented by fortifying staple food with pro-vitamin A rich plant such as pawpaw. This study evaluated the quality attributes of pawpaw fortified bread. Matured ripe pawpaw fruits were harvested, washed, peeled and blended to produce puree. Six different blends of various proportions (100:0, 90:10, 80:20, 70:30, 60:40, 50:50) of wheat and pawpaw were produced and used to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
(15 reference statements)
1
6
1
1
Order By: Relevance
“…Vitamin A was extracted from the soy-pawpaw beverage with a mixture of acetone and hexane (4:6 v/v) by the method of Singh et al (2015) and Bolarinwa et al (2020a). Ten grammes (10g) of each drink was extracted with a mixture of 20 ml of acetone and 30 ml of hexane (4/6 v/v).…”
Section: Vitamin a Determinationmentioning
confidence: 99%
See 3 more Smart Citations
“…Vitamin A was extracted from the soy-pawpaw beverage with a mixture of acetone and hexane (4:6 v/v) by the method of Singh et al (2015) and Bolarinwa et al (2020a). Ten grammes (10g) of each drink was extracted with a mixture of 20 ml of acetone and 30 ml of hexane (4/6 v/v).…”
Section: Vitamin a Determinationmentioning
confidence: 99%
“…In another study, enrichment of natural yoghurt with pawpaw was reported to produce acceptable pawpaw flavoured yoghurt with higher nutritional characteristics (Othman et al, 2019). Enrichment of white bread with pawpaw puree was also reported to improve the micronutrient contents and sensory attributes of the bread (Bolarinwa et al, 2020a). Furthermore, fortification of soymilk with carrot powder has been reported to improve the nutritive quality of soymilk (Madukwe and Eme, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The filtrate was allowed to stand for 2 h for the starch to sediment and thetp liquid was decanted and discarded. The sediment was washed and dried at 65 o C for 12 h. Beta-carotene contents of the garri sample was determined following the method of Singh et al [21] and Bolarinwa et al [22]. Briefly, The garri sample (5 g) was ground and placed in 10 ml acetone.…”
Section: Starch and Beta-carotene Content Determinationmentioning
confidence: 99%